Optical coherence tomography as retinal imaging biomarker of neuroinflammation/neurodegeneration in systemic disorders in adults and children - Vujosevic, Stela; Parra, M Margarita; Hartnett, M Elizabeth; O'Toole, Louise; Nuzzi, Alessia; Limoli, Celeste; Villani, Edoardo; Nucci, Paolo (Eye (London), 2023)
The retina and the optic nerve are considered extensions of the central nervous system (CNS) and thus can serve as the window for evaluation of CNS disorders. Spectral domain optical coherence tomography (OCT) allows for detailed evaluation of the retina and the optic nerve. OCT can non-invasively document changes in single retina layer thickness and structure due to neuronal and retinal glial cells (RGC) modifications in systemic and local inflammatory and neurodegenerative diseases. These can include evaluation of retinal nerve fibre layer and ganglion cell complex, hyper-reflective retinal spots (HRS, sign of activated microglial cells in the retina), subfoveal neuroretinal detachment, disorganization of the inner retinal layers (DRIL), thickness and integrity of the outer retinal layers and choroidal thickness. This review paper will report the most recent data on the use of OCT as a non invasive imaging biomarker for evaluation of the most common systemic neuroinflammatory and neurodegenerative/neurocognitive disorders in the adults and in paediatric population. In the adult population the main focus will be on diabetes mellitus, multiple sclerosis, optic neuromyelitis, neuromyelitis optica spectrum disorders, longitudinal extensive transverse myelitis, Alzheimer and Parkinson diseases, Amyotrophic lateral sclerosis, Huntington's disease and schizophrenia. In the paediatric population, demyelinating diseases, lysosomal storage diseases, Nieman Pick type C disease, hypoxic ischaemic encephalopathy, human immunodeficiency virus, leukodystrophies spinocerebellar ataxia will be addressed.